Finite element analysis of a low-velocity impact test for glass fiber-reinforced polypropylene composites considering mixed-mode interlaminar fracture toughness. (15th January 2017) - Jung, Ku-Hyun; Kim, Do-Hyoung; Kim, Hee-June; Park, Seong-Hyun; Jhang, Kyung-Young; Kim, Hak-Sung
Abstract: In this study, a low-velocity impact test of glass fiber-reinforced polypropylene (GFPP) composites was simulated considering interlaminar fracture toughness. In the simulation, intralaminar and interlaminar damage were modeled using the continuum damage mechanics (CDM) and cohesive zone method (CZM) models, respectively. The B-K criterion was used for the interlaminar damage model along with experimental results, which were obtained from fracture toughness tests of modes I and II and the mixed mode. Low-velocity impact tests were performed to verify the developed damage model, and various characteristics such as delamination and the force–displacement were evaluated. Finally, it was found that the developed damage model with interlaminar fracture toughness can be used to accurately predict the impact behavior of GF/PP composites, including interlaminar delamination.